2019
DOI: 10.1038/s41598-019-50194-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional metagenomic analysis of dust-associated microbiomes above the Red Sea

Abstract: Atmospheric transport is a major vector for the long-range transport of microbial communities, maintaining connectivity among them and delivering functionally important microbes, such as pathogens. Though the taxonomic diversity of aeolian microorganisms is well characterized, the genomic functional traits underpinning their survival during atmospheric transport are poorly characterized. Here we use functional metagenomics of dust samples collected on the Global Dust Belt to initiate a Gene Catalogue of Aeolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 67 publications
2
48
1
Order By: Relevance
“…These genes associated with global stress-related functions are likely acquired during sporulation formation and certainly do not result from adaptation of fungi in air. When studying genes coding more specific proteins that are not associated with spore resistance, such as lipoate synthase and chromosome plasmid partitioning protein ParA, which might play a role in oxidative stress (Allary et al, 2007;Bunik, 2003) and are more generally found in stress resistance and adaptability of microorganisms (Shoeb et al, 2012;Zhang et al, 2018), they were occasionally found in relatively high concentrations in air samples (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes associated with global stress-related functions are likely acquired during sporulation formation and certainly do not result from adaptation of fungi in air. When studying genes coding more specific proteins that are not associated with spore resistance, such as lipoate synthase and chromosome plasmid partitioning protein ParA, which might play a role in oxidative stress (Allary et al, 2007;Bunik, 2003) and are more generally found in stress resistance and adaptability of microorganisms (Shoeb et al, 2012;Zhang et al, 2018), they were occasionally found in relatively high concentrations in air samples (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…Given that cultivable organisms represent about 1 % of the entire microbial community (Vartoukian et al, 2010), culture-independent techniques and especially metagenomic studies applied to atmospheric microbiology have the potential to provide additional information on the selection and genetic adaptation of airborne microorganisms. However, to our knowledge, only five metagenomic studies on airborne microbial communities at one or two specific sites per study exist (Aalismail et al, 2019;Cao et al, 2014;Gusareva et al, 2019;Yooseph et al, 2013). Metagenomic investigations of complex microbial communities in many ecosystems (for example, soil, seawa-Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…microorganisms. However, to our knowledge, only five metagenomic studies on airborne microbial communities at one or two specific sites per study exist (Aalismail et al, 2019;Amato et al, 2019;Cao et al, 2014;Gusareva et al, 2019;Yooseph et al, 2013). Metagenomic investigations of complex microbial communities in many ecosystems (for example, soil, seawater, lakes, feces, sludge) have provided evidence that microorganism functional signatures reflect the abiotic conditions of their environment, with different relative abundances of specific microbial functional classes (Delmont et al, 2011;Li et al, 2019;Tringe et al, 2005;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, airborne microbial activity-related investigations have been mainly carried out on microorganisms isolated from cloud water where chemical species are in solution. Although a high diversity in functional genes has been revealed from planetary boundary layer microbial metagenomes [135,136], (Tignat-Perrier et al, in revision), the significance of planetary boundary layer microbial activity on atmospheric chemistry remains unknown.…”
Section: Potential Impacts Of Airborne Microbial Activity On Atmosphementioning
confidence: 99%